Municipal water and wastewater treatment - Kumar, Rakesh; Singh, R.N.; Ramachandra, T. V. (ed.) (New Delhi TERI Press, 2020)
The book provides an overview of the engineering approaches towards ensuring water quality, with an emphasis on fundamental principles. It presents water quality objectives and the chemical, physical, and biological processes necessary for designing and managing drinking water and waste water treatment plants. Theory and conceptual designs of systems for treating municipal waste water and drinking water are discussed. The basic principles of common treatment processes are also discussed.
Keywords: Municipal water supply; Sewage-Purification